KIF26B Is Overexpressed in Medulloblastoma and Promotes Malignant Progression by Activating the PI3K/AKT Pathway - Yajun Liu; Xi Zhang; Ruihan Pan; Xiaolong Liang; Qichang Liu; Chao Yang; Xu Li (Analytical Cellular Pathology)
Medulloblastoma is one of the most common malignant tumors of the central nervous system in children. Although KIF2B was reported as an oncogene in several malignant tumor types, its role in medulloblastoma has not been studied so far. The PCR results of our study showed that KIF26B is highly expressed in medulloblastoma, and its high expression is associated with a high clinical stage. Knockdown the expression of KIF26B could significantly impair the proliferation and migration of medulloblastoma cells. KIF26B promotes the malignant progression of medulloblastoma by affecting the expression of phosphorylation of key proteins in the PI3K/AKT signaling pathway. With the help of 740 Y-P, activating the pi3k signaling pathway can partially rescue the phenotype. Therefore, our experimental results suggest that KIF26B is a potential target for medulloblastoma.